Multi-Criteria Analysis Approach for Potential Flood Areas Mapping in The Bedadung River Watershed, Jember Regency - Wafi, Moh. Abduh; Cahyono, Bowo Eko; Octaviani, Linggar Ayu; Triatmojo, Muhammad Ikbal Nur Dian; Suprianto, Agus (Department of Geography Education, University of Jember, 2024)
Flood disasters often result in negative impacts, including damage to property, infrastructure, and loss of human lives. Identifying flood-prone areas and implementing appropriate prevention measures can significantly reduce its adverse effects. Mapping potential flood plays a key role in land use planning, early warning systems, emergency response, and flood mitigation efforts. In recent years, the Bedadung Watershed has faced issues of fluctuations in water discharge and it has a potential to cause flooding in Jember regency. This study aims to assess the flood vulnerability level in the Bedadung Watershed using parameter’s scoring and weighting methods, followed by an overlay or merging of each parameter. The research findings indicate that parameters influencing flood potential in the Bedadung Watershed are land use and land cover, slope and elevation area, and soil type. The results showed that the areas which are identified as vulnerable and highly vulnerable are mainly located at low elevations (0-500 m) with tend to be safe from occurring flood even though the level of rainfall is high. On the other side, the vegetation cover areas showed the low vulnerable from flood.